ФІЛОСОФСЬКО-РЕЛІГІЙНИЙ ЗМІСТ ФЕНОМЕНУ ПОДВИЖНИЦТВА - Гончаров, Г. М. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2015)
Ця стаття присвячена проблемі наукового підходу у вивченні феномена подвижницкої діяльностіта подвига за своєю суттю проблемі дійсного пізнання людиною Істини і буття в цілому, коли разом з подвижницьким методом пізнання, що існує в самій подвижницькій традиції, формується методпізнання, використовуваний при філософсько-теоретичній концептуалізації. Гончаров Г.М. Философско-религиозный смысл феномена подвижничества. Эта статья посвящена проблеме научного подхода в изучении феномена подвижнической деятельности и подвига по своей сути проблеме истинного познания человеком Истины и бытия в целом, когда наряду с подвижническим методом познания, существующим в самой подвижнической традиции, формируется метод познания, используемый при философско-теоретической концептуализации. Ключевые слова: подвижничество, мистико-аскетический опыт, антропологический предел,синергия.Goncharov G.M. Рhilosophical-religious sense of the phenomenon of selfless devotion. This article issacred to the problem of scientific approach in the study of the phenomenon of selfless activity and exploit on theessence to the problem of veritable cognition of Truth and life a man on the whole, when along with the selflessmethod of cognition, existing in the most selfless tradition, the method of cognition, used for philosophicaltheoreticalconception, is formed.Keywords: selfless devotion, mystery-ascetic experience, anthropological limit, synergy.